2018
DOI: 10.5530/ijper.52.4.75
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Evaluation of 4-Aminopyridine Analogues as Cholinesterase Inhibitors for Management of Alzheimer’s Diseases

Abstract: Introduction: Alzheimer's disease (AD) is a slowly progressive devasting neurodegenerative disorder of central nervous system manifested by deterioration of memory, cognitive functions, behaviour change and impairment in performing activities of daily life. Neurochemical studies of patients suffering from AD demonstrate selective loss of cholinergic neurons, low concentration of acetylcholine (Ach) in the selective areas of brain such as cortex and hippocampus. Objective: A series of new semicarbazones of 4-am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In solution these tautomeric equilibria depend strongly on some structural factors such as substitution pattern and intramolecular hydrogen bonding, and are also markedly influenced by temperature, light and solvent effects. 19 However, Schiff bases of THB with aromatic amines ( 14 , R = aryl), 20 hydrazines ( 14 , R = NR 1 R 2 ) 21 and hydrazides ( 14 , R = COR 1 ), 22 (thio)semicarbazides ( 14 , R = NHCONH 2 or NHCSNH 2 ), dithiocarbazides ( 14 , R = NHCSS-R 1 ) and carbohydrazides, 22 show exclusively imine structures in solution.…”
Section: Introductionmentioning
confidence: 99%
“…In solution these tautomeric equilibria depend strongly on some structural factors such as substitution pattern and intramolecular hydrogen bonding, and are also markedly influenced by temperature, light and solvent effects. 19 However, Schiff bases of THB with aromatic amines ( 14 , R = aryl), 20 hydrazines ( 14 , R = NR 1 R 2 ) 21 and hydrazides ( 14 , R = COR 1 ), 22 (thio)semicarbazides ( 14 , R = NHCONH 2 or NHCSNH 2 ), dithiocarbazides ( 14 , R = NHCSS-R 1 ) and carbohydrazides, 22 show exclusively imine structures in solution.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction showed below in figure 30 represents the semicarbazones of 4-aminopyridine synthesis. Singh and co-workers opined that the in-vitro study of synthesized analogues showed maximum activity of compounds compared to standard drug rivastigmine [52]. They reported that the enzyme kinetic study revealed a non-competitive inhibition of acetylcholinesterase (AChE) and is responsible for the possible interaction of the analogue with the peripheral anionic site (PAS) of AChE, which was however confirmed by molecular docking studies.…”
Section: Semicarbazones Of 4-aminopyridinementioning
confidence: 99%
“…The synthesis of semicarbazones of 4-aminopyridine was obtained by the reaction of 5ml of glacial acetic acid solution of 4-aminopyridine and NaCNO in 25ml of warm water was conducted by Singh et al [52]. The mixture was stirred and allowed to stand for 4 hours, thereafter; the product was obtained by filtration, washed with water, dried in an oven below the melting point and recrystallized from ethanol to afford key intermediate.…”
Section: Semicarbazones Of 4-aminopyridinementioning
confidence: 99%
See 1 more Smart Citation
“…The hydroxyl group of one of these compounds' phenyl rings was observed forming an H-bond with Tyr-70 in docking studies, and Tyr-70 appears to play a dual role in the active centre: (a) its hydroxyl appears to maintain the functional orientation of Phe-288 and Tyr-70 by hydrogen bonding, and (b) its aromatic moiety appears to maintain the functional orientation of the anionic subsite Trp-84. Compounds 286 and 287 were discovered as the most potent species in an AChE inhibition and passive avoidance test, which could lead to the discovery of new cognition enhancers soon 281 ( Table 13 ).…”
Section: Synthetic Cholinesterase Inhibitorsmentioning
confidence: 99%